How do workplaces, working practices and colleagues affect UK doctors’ career decisions? A qualitative study of junior doctors’ career decision making in the UK - Spooner, Sharon (BMJ Open, 2017)
OBJECTIVES: This study draws on an in-depth investigation of factors that influenced the career decisions of junior doctors. SETTING: Junior doctors in the UK can choose to enter specialty training (ST) programmes within 2 years of becoming doctors. Their specialty choices contribute to shaping the balance of the future medical workforce, with views on general practice (GP) careers of particular interest because of current recruitment difficulties. This paper examines how experiences of medical work and perceptions about specialty training shape junior doctors’ career decisions. PARTICIPANTS: Twenty doctors in the second year of a Foundation Training Programme in England were recruited. Purposive sampling was used to achieve a diverse sample from respondents to an online survey. RESULTS: Narrative interviewing techniques encouraged doctors to reflect on how experiences during medical school and in medical workplaces had influenced their preferences and perceptions of different specialties. They also spoke about personal aspirations, work priorities and their wider future. Junior doctors’ decisions were informed by knowledge about the requirements of ST programmes and direct observation of the pressures under which ST doctors worked. When they encountered negative attitudes towards a specialty they had intended to choose, some became defensive while others kept silent. Achievement of an acceptable work-life balance was a central objective that could override other preferences. Events linked with specific specialties influenced doctors’ attitudes towards them. For example, findings confirmed that while early, positive experiences of GP work could increase its attractiveness, negative experiences in GP settings had the opposite effect. CONCLUSIONS: Junior doctors’ preferences and perceptions about medical work are influenced by multiple intrinsic and extrinsic factors and experiences. This paper highlights the importance of understanding how perceptions are formed and preferences are developed, as a basis for generating learning and working environments that nurture students and motivate their professional careers.